Meningkatkan Prestasi Belajar Matematika dengan Pendekatan CTL - Sulasmi, Sulasmi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2016)
Lower mathematics learning achievement was anxiety for teachers which should be repaired. Through this research teacher wanted knew mathematics learning achievement through CTL approach. Based on CTL theory said that CTL believed that could be improve learning achievement, through contructivism approach and learning society. This research was conducted at class VII on Wednesday. October 7th 2009 1,2 o’clock in cycle I and cycle II on October 21st 2009 1,2 o’clock. In this research, researcher used test and observation sheet, then data was analyzed by descriptive quantitative. Based on data analysis descriptive qualitative learning achievement improved in cycle I mean score was 53,5 with students’ completeness was 4 students and students who not completeness was 21 students, in cycle II students who completeness was 31 students and not completeness was 4 students. In implementing CTL teachers could conduct well on 6 stages in cycle I and cycle II. So that CTL approach could improve students’ mathematics learning achievement. The result of this research was hoped could be used for teachers on pedagogic services and for school it could improve quality and learning services.